Photophysical and photochemical studies of non-transition metal phthalocyanine derivatives - Ogunsipe, Abimbola Olukayode (Rhodes University, Faculty of Science, Department of Chemistry, 2005)
A detailed photophysicochemical study of some non-transition metal (AI, Zn, Si, Ge, and Sn) metallophthalocyanine (MPc) derivatives is presented. The effects of substituents, central metal ions and solvents on the photophysical and photochemical properties are investigated and rationalized accordingly. The presence of peripheral substituents on the macrocycle enhances the yield of the triplet state. Near infra-red absorptions of the solvents reveal that solvents which absorb around 1100 nm and around 1270 nm, quench the triplet state of the MPc derivative and singlet oxygen, respectively. Although water has a high singlet oxygen quenching effect, the singlet oxygen quantum yield (Φ∆) value for sulphonated zinc phthalocyanine in water is still reasonably high at 0.48, which may provide an explanation for the efficient photosensitization by this molecule in photodynamic studies. The lowering of Φ∆ following protonation of the MPc macrocycle is attributed to the lowering of triplet energy to the level where energy transfer to ground state oxygen is no longer favourable. MPc inclusion complexes with cyclodextrins showed larger Φ∆ values when compared to the complexes before inclusion. Job's plots show that 2:1 and 4:1 (CD:MPc) complexes may be formed. Fluorescence quenching by electron donors and acceptors were analysed by StemVolmer relationship and the results used in determining fluorescence lifetimes of the complexes. Qualitative and quantitative interpretations of the interaction of sulphonated MPcs with bovine serum albumin (BSA) are provided in this thesis. 1:1 adducts were formed with BSA, but the binding feasibilities varied markedly. Spectral, photophysical and photochemical properties of the complexes are altered in the presence of BSA.
Keywords: Photochemotherapy; Phthalocyanines; Spectrum analysis